Left ventricular hypertrophy is a predictor of cardiovascular events in elderly hypertensive patients: Hypertension in the Very Elderly Trial. Issue 11 (November 2016) - Antikainen, Riitta L.; Peters, Ruth; Beckett, Nigel S.; Fagard, Robert H.; Wang, Ji-Guang; Rajkumar, Chakravarthi; Bulpitt, Christopher J.
Abstract : Objective: We assessed the prognostic value of ECG left ventricular hypertrophy (LVH) using Sokolow–Lyon (SL-LVH), Cornell voltage (CV-LVH) or Cornell product (CP-LVH) criteria in 3043 hypertensive people aged 80 years and over enrolled in the Hypertension in the Very Elderly Trial. Methods: Multivariate Cox proportional hazard models were used to estimate hazard ratios with 95% confidence intervals (CIs) for all-cause mortality, cardiovascular diseases, stroke and heart failure in participants with and without LVH at baseline. The mean follow-up was 2.1 years. Results: LVH identified by CV-LVH or CP-LVH criteria was associated with a 1.6–1.9-fold risk of cardiovascular disease and stroke. The presence of CP-LVH was associated with an increased risk of heart failure (hazard ratio 2.38, 95% CI 1.16–4.86). In sex-specific analyses, CV-LVH (hazard ratio 1.94, 95% CI 1.06–3.55) and CP-LVH (hazard ratio 2.36, 95% CI 1.25–4.45) were associated with an increased risk of stroke in women and of heart failure in men, CV-LVH (hazard ratio 6.47, 95% CI 1.41–29.79) and CP-LVH (10.63, 95% CI 3.58–31.57), respectively. There was no significant increase in the risk of any outcomes associated with Sokolow–Lyon-LVH. LVH identified by these three methods was not a significant predictor of all-cause mortality. Conclusion: Use of Cornell voltage and Cornell product criteria for LVH predicted the risk of cardiovascular disease and stroke. Only Cornell product was associated with an increased risk of heart failure. This was particularly the case in men. The identification of ECG LVH proved to be important in very elderly hypertensive people.